FREE INVERSION AND RAISING TO OBJECT IN ROMANIAN INFINITIVE CLAUSES: AN EXFOLIATION APPROACH (Theoretical and Applied Linguistics@ro, 2025)
The paper examines Romanian raising infinitives in the framework of Exfoliation (Pesetsky 2021). At first sight, Romanian appears to be a direct counterexample to the Exfoliation analysis since it does not show the expected correlation between infinitivization and the extraction of the subject. Two different infinitive patterns occur with raising verbs. a) The first is similar to the English pattern. The lower subject raises as an Accusative in the main clause and may cliticize on the main verb. The clitic is doubled by a strong accusative pronoun or a DOM-ed DP. b) This expected pattern alternates, however, with another infinitive construction, where the subject of the infinitive clause appears in postverbal position in the infinitive clause and bears Nominative case. Since the subject has not been extracted, the low Nom sentences should have been finite.We propose that low Nominative subjects are examples of Free Inversion. In Belletti’s 2005 analysis, Free Inversion requires the formation of an < proexpl…DPNom > chain. And for low Nom sentences under Raising triggering verbs, it is the expletive pro that raises, leaving the Nom in the lower clause. The fact that the lower subject is marked as Nominative is natural since the clause starts out as a finite clause, where Case is regularly assigned.
Keywords: Exfoliation; raising; free inversion; covert raising